Preserved VPS13A distribution and expression in Huntington’s disease: divergent mechanisms of action for similar movement disorders? - García-García, Esther; Carreras-Caballé, Maria; Coll-Manzano, Albert; Ramón-Lainez, Alba; Besa-Selva, Gisela; Pérez-Navarro, Esther; Malagelada, Cristina; Alberch, Jordi; Masana, Mercè; Rodríguez, Manuel J. (Frontiers in Neuroscience, 2024)
VPS13A disease and Huntington's disease (HD) are two basal ganglia disorders that may be difficult to distinguish clinically because they have similar symptoms, neuropathological features, and cellular dysfunctions with selective degeneration of the medium spiny neurons of the striatum. However, their etiology is different. VPS13A disease is caused by a mutation in the VPS13A gene leading to a lack of protein in the cells, while HD is due to an expansion of CAG repeat in the huntingtin (Htt) gene, leading to aberrant accumulation of mutant Htt. Considering the similarities of both diseases regarding the selective degeneration of striatal medium spiny neurons, the involvement of VPS13A in the molecular mechanisms of HD pathophysiology cannot be discarded. We analyzed the VPS13A distribution in the striatum, cortex, hippocampus, and cerebellum of a transgenic mouse model of HD. We also quantified the VPS13A levels in the human cortex and putamen nucleus; and compared data on mutant Htt-induced changes in VPS13A expression from differential expression datasets. We found that VPS13A brain distribution or expression was unaltered in most situations with a decrease in the putamen of HD patients and small mRNA changes in the striatum and cerebellum of HD mice. We concluded that the selective susceptibility of the striatum in VPS13A disease and HD may be a consequence of disturbances in different cellular processes with convergent molecular mechanisms already to be elucidated.